Perancangan Interior Healthy Day Care di Surabaya - Shirley Vionita Chandra (Intra, 2017)
Healthy Day Care is a child care center which designed with priority of children's health that applied to all room elements which designed with healthy and attractive design that its application is done by making the formation, color, circulation space, lighting, which draw the attention of the child to can do their activities cheerfully but not excessive. Healthy Day Care is designed to solve the problem of any women who has some problems with her children, seeing the health of children today that are declining due to less activity and less socializing with the surrounding environment. Healthy Day Care must also be able to meet the basic needs of children to achieve the design results in accordance with the original purpose.